L’évolution des politiques de protection et l’intégration du secteur privé dans la conservation - Mara Sierra Jimenez (Caravelle)
The model of concession was started in Colombia since 2005. This management strategy tries to advantage the territories’ economical development as well as the conservation of heritages. Amacayacu National Park, in the Colombian Amazon, was a pioneer in this novelty which shows its complexity by the superimposition of the National Park and the heterogeneity of Indian territories. This article aims to present the stages of the concession’s application, its advantages, its limits and its consequences on local communities.